The safety and feasibility of endoscopic submucosal dissection using a flexible three‐dimensional endoscope for early gastric cancer and superficial esophageal cancer: A prospective observational study. Issue 4 (9th February 2022) - Shinmura, Kensuke; Yamamoto, Yoichi; Inaba, Atsushi; Okumura, Kei; Nishihara, Keiichiro; Kumahara, Kana; Sunakawa, Hironori; Furue, Yasuaki; Ito, Renma; Sato, Daiki; Minamide, Tatsunori; Suyama, Masayuki; et al.
Abstract: Background and Aim: Endoscopic submucosal dissection (ESD) is performed as one of standard treatments for patients with early gastric cancer (EGC) and superficial esophageal squamous cancer (SESCC). A prototype of a flexible endoscope with a 3‐D system has been recently developed. This study aimed to investigate the safety and feasibility of ESD using a 3‐D flexible endoscope (3‐D ESD) for EGC and SESCC. Methods: This single‐center, prospective, observational study enrolled patients who underwent planned 3‐D ESD. The clinical outcomes, including the incidence of adverse events and treatment results, were analyzed. Visibility and manipulation during 3‐D ESD were evaluated using a visual analog scale (VAS). We also evaluated the effect of the 3‐D system on the endoscopist using VAS and the critical flicker fusion frequency (CFFF). Results: We analyzed 47 EGC and 20 SESCC cases. There are no bleeding cases that required transfusion and perforation during 3‐D ESD in both EGC and SESCC patients. However, the incidence of delayed bleeding and delayed perforation was 1.5% (one case) each. The mean VAS scores for recognizing the submucosal layer during the submucosal dissection, visual perception of blood vessel, and depth perception were 72.7 ± 22.2, 74.7 ± 21.8, and 78.2 ± 19.9, respectively. In contrast, the mean VAS score for manipulation was 25.4 ± 19.7. Among endoscopists, there was no significant difference in the VAS of eyestrain and headache before and after ESD, and there was no significant difference in the CFFF. Conclusion: The safety and feasibility of 3‐D ESD for EGC and SESCC are acceptable in both patients and endoscopists.